Independent audit committee, risk management committee, and audit fees - Dyah Ayu Larasati; Melinda Cahyaning Ratri; Mohammad Nasih; Iman Harymawan (Cogent Business & Management, 2019)
This study aims to analyze the role of an independent audit committee on the relationship between the Risk Management Committee (RMC) and audit fees. We use 510 observations from 216 different companies indexed on the Indonesia Stock Exchange for 2014-2016. This study uses ordinary least square analysis to prove our hypotheses. We find that participation of the independent commissioner as an audit committee member will strengthen the relationship between RMC and audit fee. Consistent with the demand side of audit theory, our study shows that the existence of a stand-alone risk management committee and a more independent commissioner sitting on the audit committee will demand higher audit coverage. As a result, it will increase the audit fee. It occurs since the existence of a more independent audit committees could be able to objectively assess the risk as recommended by the RMC and respond to it by increasing the demand on audit coverage for higher audit quality, and hence increase the fees paid to the external auditor. These findings could contribute to the regulatory bodies in Indonesia in terms of providing empirical evidence on the relationship between board governance structure and audit pricing within non-financial industries companies.
Keywords: G32; G34; 650; risk management committee; board risk committee; independent audit committee; audit fees